Selective Propargylation of Diaryl Azo Compounds Using Metallic Barium - Yanagisawa, Akira; Heima, Toshihiko; Watanabe, Kana; Haeno, Shun (Synlett, 2020)
The Barbier-type propargylation of azo compounds with α,γ-disubstituted propargylic tosylates was achieved by using metallic barium as the promoter. Various propargylated hydrazines (α-adducts) were exclusively synthesized from the corresponding propargylic tosylates and azobenzenes (diaryldiazenes). The thus-obtained propargylic hydrazines were further efficiently converted into propargylic amines by reductive N–N bond cleavage. Benzidine rearrangement of the propargylic hydrazines was also attempted.
Keywords: azo compounds; barium; hydrazines; propargylation; propargylic tosylates